2014
DOI: 10.1038/srep07218
|View full text |Cite
|
Sign up to set email alerts
|

The role of different social contexts in shaping influenza transmission during the 2009 pandemic

Abstract: Evaluating the relative importance of different social contexts in which infection transmission occurs is critical for identifying optimal intervention strategies. Nonetheless, an overall picture of influenza transmission in different social contexts has yet to emerge. Here we provide estimates of the fraction of infections generated in different social contexts during the 2009 H1N1 pandemic in Italy by making use of a highly detailed individual-based model accounting for time use data and parametrized on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 42 publications
5
38
2
Order By: Relevance
“…By assuming that containment measures are implemented from the very beginning of the outbreak, we estimate that the probability of disease elimination could have been as high as 99.0 % (95 % CI, 98.8–99.2) as a combined result of isolation of cases and contact tracing as performed in Pujehun district. We found that 74.3 % of transmission events occurred between members of the family (a percentage about three times higher than that of influenza [ 10 , 11 ]) or extended family and most of the remaining transmission occurred between friends – a pattern similar to that found in Guinea [ 12 ] and ascribable to the fact that EVD is mainly transmitted through unprotected physical contacts. Therefore, contact investigation could have been facilitated by close social and demographic relationships between cases.…”
Section: Discussionsupporting
confidence: 53%
“…By assuming that containment measures are implemented from the very beginning of the outbreak, we estimate that the probability of disease elimination could have been as high as 99.0 % (95 % CI, 98.8–99.2) as a combined result of isolation of cases and contact tracing as performed in Pujehun district. We found that 74.3 % of transmission events occurred between members of the family (a percentage about three times higher than that of influenza [ 10 , 11 ]) or extended family and most of the remaining transmission occurred between friends – a pattern similar to that found in Guinea [ 12 ] and ascribable to the fact that EVD is mainly transmitted through unprotected physical contacts. Therefore, contact investigation could have been facilitated by close social and demographic relationships between cases.…”
Section: Discussionsupporting
confidence: 53%
“…We considered as reference scenario a situation comparable to the experience of the United Kingdom during the 2009 A/H1N1 influenza pandemic: we therefore assumed a basic reproductive number R 0 = 1.5 (see [ 55 ] for a systematic review), probability of developing symptoms given infection was set to 30%, in line with findings reported in [ 56 ], and adults were assumed to be half as susceptible to infection as children [ 33 , 57 , 58 ]. Other assumptions are explained in the Methods section and in the Supporting Text.…”
Section: Resultsmentioning
confidence: 99%
“…During regular school days, the transmission can occur in each of the three layers, while during the summer holidays no transmission at school is possible. Layer-specific weights regulating the transmission process in each layer were estimated from the Italian time-use data by assuming that the transmission probability is proportional to the time spent in contact with other individuals [54]. The latent period, the infectious period, and the case importation rate were the same as for the other models.…”
Section: Experiments Designmentioning
confidence: 99%